Cognitive interviews for measurement evaluation of the Fagerström Test for Nicotine Dependence (FTND) in smokers with schizophrenia spectrum disorders - Prochaska, Judith J.; Leek, Desiree N.; Hall, Stephen E.; Hall, Sharon M. (Addictive behaviors, 2007)
People diagnosed with schizophrenia have among the highest known rates of tobacco use. While the Fagerström Test for Nicotine Dependence (FTND) is the most widely used measure of nicotine dependence, recent research has questioned its applicability for individuals with schizophrenia. The current study employed cognitive interviews to evaluate the FTND with smokers diagnosed with schizophrenia spectrum disorders, recruited from an acute inpatient psychiatry setting, and a comparison group of smokers recruited from the community. The groups were comparable on tobacco use variables and FTND scores. Detailed qualitative cognitive interviews indicated all subjects understood the FTND items. For both groups, the FTND missed nocturnal smoking, reported as weekly by 80% of patients and 47% of controls. Finishing other people's cigarettes also was under-reported on the FTND. Restrictions to smoking were common across groups. The cognitive interview methodology proved useful for understanding how individuals interpreted and answered the FTND items. Overall, the qualitative findings identified limitations in the FTND for both groups, with the limitations generally more pronounced among patients with schizophrenia.